A223 OPTIMIZING CO-MANAGEMENT OF PANCREATIC ENZYME INSUFFICIENCY: A CANADIAN CONSENSUS. (15th March 2019) - Donnellan, F; Baillargeon, D; Teshima, C W
Abstract: Background: Pancreatic enzyme insufficiency (PEI) arises from a variety of causes in various pathologic states, including inborn disease (notably cystic fibrosis (CF)); pancreatic duct obstruction, e.g., due to local tumour growth; and chronic pancreatitis (CP). PEI can therefore arise at any time in life, from infancy to advanced old age, and it presents clinically with a relatively non-specific constellation of gastrointestinal (GI) symptoms and laboratory findings, all associated with maldigestion and malabsorption. Signs and symptoms of PEI can be managed with pancreatic enzyme replacement therapy (PERT). For most forms of PEI, primary care physicians (PCPs) are likely to be the first to identify these signs and symptoms and to make a preliminary diagnosis. Aims: A Canadian Expert Panel has recently published a consensus guidance document on PEI diagnosis and management. The Panel's recommendations have clear implications for PCPs who refer patients with suspected PEI or who need to co-manage patients with this condition. Here, we describe and comment on the Panel's recommendations that guide GI specialists' interactions with PCPs. Methods: Key questions about PEI were identified by the Panel and researched in the clinical literature. The Panel reviewed the findings and developed consensus recommendations related to: diagnostic features of PEI; conditions that increase the index of suspicion of PEI; screening of patients considered at elevated risk of PEI; investigations that should be carried out at the PCP level and communicated to the GI specialist via a referral letter; principles of PERT and PERT optimization; dietary and lifestyle advice for patients with PEI. Results: Key diagnostic features of PEI include steatorrhea, unexplained weight loss, and specific micronutrient deficiencies. Predisposing conditions include CP, CF, type 1 diabetes, HIV/AIDS, celiac disease, and surgical resection in or near the pancreas. Other causes, including pancreatic cancer, may warrant urgent specialist referral for investigation. Patients with PEI typically should not be encouraged to reduce or avoid dietary fat but should be treated to improve their tolerance of a normal diet. Trial use of PERT may be considered by PCPs, particularly if wait time for GI specialist access is long. Response to treatment, along with other relevant aspects of patient history, should be communicated at the time of referral. Conclusions: Educational efforts should be directed to both GI specialists and PCPs to facilitate co-management of patients with confirmed or suspected PEI. Funding Agencies: This manuscript was funded by BGP Pharma ULC.